Effectiveness of acyclovir in the treatment of pityriasis rosea. A systematic review and meta-analysis - Milton Rodriguez-Zuniga; Natalie Torres; Herney Garcia-Perdomo (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: There is a lack of evidence to support acyclovir administration in pityriasis rosea. Objective: To determine the efficacy of acyclovir in patients with typical pityriasis rosea. Methods: A systematic review and meta-analysis of experimental studies was performed in MEDLINE, SCOPUS, EMBASE and others, from January 1990 to October 2016 on acyclovir for pityriasis rosea. Random effect model was used to find the pooled Risk Ratio. Outcomes, evaluated between weeks 1 to 8, were regression of lesions, cessation of lesions, decrease of symptoms and duration of disease. Comparisons were acyclovir vs. placebo; acyclovir vs. symptomatic treatment; acyclovir vs. antibiotic; acyclovir vs. observation and combined therapy (acyclovir plus symptomatic treatment) vs. symptomatic treatment alone. Results: Seven papers were analyzed with 324 participants, of which 159 received acyclovir and 165 were controls. Acyclovir was superior to placebo for complete regression of lesions at week 1 (Risk Ratio 5.72, CI95% 2.36-13.88). However, combined therapy was not superior to symptomatic treatment at week 4 (Risk Ratio 1.46, CI95% 0.93-2.29). Individual studies showed the superiority of acyclovir for the control of symptoms and pruritus. Study limitations: We faced differences designs of trials and inconsistency between reports. Conclusion: Symptomatic treatment is a reasonable option for pityriasis rosea, and the addition of acyclovir is justified for the control of symptoms and pruritus.